A systematic review of the relationship between emotion and susceptibility to misinformation. Issue 1 (2nd January 2023) - Sharma, Prerika R.; Wade, Kimberley A.; Jobson, Laura
ABSTRACT: Inaccurate memory reports can have serious consequences within forensic and clinical settings, where emotion and misinformation are two common sources of memory distortion. Many studies have investigated how these factors are related; does emotion protect memory or leave it more vulnerable to the distorting effects of misinformation? The findings remain diffused. Thus, the present review aimed to clarify the relationship between emotion and susceptibility to misinformation. 39 eligible studies were reviewed. Results varied according to the type and dimension of emotion measured. Level of arousal may be unrelated to susceptibility to misinformation when retrieval occurs without delay; studies including delayed retrieval were limited. Stimuli valence may be associated with increased susceptibility to peripheral misinformation but unrelated to other misinformation. The following results were reported by limited studies: short-term distress and moderate levels of stress may decrease susceptibility, while anger and greater cortisol response to stress may increase susceptibility to misinformation. Source memory may also be unaffected by emotion. The results have important potential implications for forensic and clinical practice, for example by highlighting the value of enquiring witnesses' source memory. Methodological recommendations for future studies are made.